How a broken vertebra can lead to a fatal hemorrhage: a case report - Roxanne A. W. Ploumen; Martin R. van Wezenbeek; Paul C. P. H. Willems; Suzanne C. Gerretsen; Jan A. Ten Bosch (International Journal of Emergency Medicine, 2024)
Abstract Background Unintentional falls are common among the elderly and given the expected increase of the aging population, these falls contribute to a high number of admissions to the emergency department. Relatively low-energy trauma mechanisms can lead to serious injuries in the elderly, with contributing factors being comorbidities, medication use and degenerative abnormalities. Case presentation A 94-year-old female suffered an unintentional fall at home. Upon arrival of the ambulance at her house she was hemodynamically stable and mobilized to the gurney with assistance. During primary survey at the emergency department, her blood pressure and oxygen saturation decreased, she was not able to move her legs anymore and lost consciousness. A full-body CTA was performed, which showed a fracture through the vertebral body of L2 with significant dislocation and a large active bleeding of the corpus, extending to the retroperitoneum and the epidural space. Despite resuscitation, her vital signs deteriorated and given the severe abnormalities on CTA, it was decided to discontinue further treatment, after which she deceased. The performed CTA and an x-ray from 2016 suggested diffuse idiopathic skeletal hyperostosis, which might have contributed to the severity and instability of the vertebral fracture. Mobilization after the fall might have increased the dislocation of the fracture. The use of oral anticoagulants worsened the subsequent bleeding and the extension to the epidural space caused the paralysis of the legs. Conclusions It is important to be aware of the possible serious consequences of unintentional falls in the elderly population and to provide strict immobilization of the spinal column until proper imaging.